2015
DOI: 10.4018/ijcwt.2015070103
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Human Operators' Suspicion in the Detection of Cyber Attacks

Abstract: Despite the importance that human error in the cyber domain has had in recent reports, cyber warfare research to date has largely focused on the effects of cyber attacks on the target computer system. In contrast, there is little empirical work on the role of human operators during cyber breaches. More specifically, there is a need to understand the human-level factors at play when attacks occur. This paper views cyber attacks through the lens of suspicion, a construct that has been used in other contexts, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…This leads to the conclusion that the attack evokes cognitive activation as described in the deception detection model (Grazioli, 2004), which increases the workload. This result is consistent with previous research by Hirshfield et al (2015), who also reported increased workload when users are under cyber-attack.…”
Section: Workload (Rq 1 and Rq 2)supporting
confidence: 83%
See 4 more Smart Citations
“…This leads to the conclusion that the attack evokes cognitive activation as described in the deception detection model (Grazioli, 2004), which increases the workload. This result is consistent with previous research by Hirshfield et al (2015), who also reported increased workload when users are under cyber-attack.…”
Section: Workload (Rq 1 and Rq 2)supporting
confidence: 83%
“…Different models and views all suggest that such an analytic procedure places severe demands on cognitive resources (Bobko et al, 2014;Boyce et al, 2011;Dutt et al, 2013;Grazioli, 2004;Hirshfield et al, 2015;Rasmussen, 1983). Further, Orasanu et al (1993) argue that ambiguous cues such as those, we argue, present during a cyber-attack also increase workload.…”
Section: Research Questionsmentioning
confidence: 99%
See 3 more Smart Citations